Students' Perception of Studying English at The Twelfth Grade Students SMN N 8 Jambi City. - Riska Liansari; Wennyta Wennyta; Yanti Ismiyati (JELT: Journal of English Language Teaching, 2021)
This study aims to determine students' perceptions about learning English in the twelfth grade of senior high school 8 in the city of Jambi. This research is a qualitative phenomenological research. The data collection technique was obtained through interviews. The results showed that according to students learning English is very easy to understand if students want to learn to understand it, the interest of students of SMAN 8 Jambi city in receiving learning is also supported by learning support facilities such as books, English dictionaries, and other online English dictionary sites. In addition, the assignment given by the teacher also raises student perceptions. Good teacher interaction in delivering learning can also lead to student perceptions. In this case the teachers at SMAN 8 Kota Jambi always use two languages to interact with their students. Good interaction between students and teachers is also supported by student activities. In this case, students of SMAN 8 Jambi City are always actively asking their teachers and friends about learning English. As for its application in everyday life, due to the lack of students 'ability in English pronunciation, and the lack of students' vocabulary regarding English learning, students lack confidence to interact with other people in using English. Based on the research results, it can be concluded that according to students learning English is very easy. Students' interest in receiving learning is also supported by supporting facilities for learning English such as books and dictionaries. Teachers always use two languages to interact with their students in learning English, namely by mixing Indonesian. Students always actively ask teachers and friends about learning English that students do not know, and students do not apply English in their daily life due to lack of vocabulary and lack confidence in interacting with other people in using English.Keywords: Students' Perception, Studying English